Rare Copy Number Variations and Predictors in Children With Intellectual Disability and Epilepsy - Kessi, Miriam; Xiong, Juan; Wu, Liwen; Yang, Lifen; He, Fang; Chen, Chen; Pang, Nan; Duan, Haolin; Zhang, Wen; Arafat, Ahmed; Yin, Fei; Peng, Jing (Frontiers in Neurology, 2018)
Introduction: The concurrence of intellectual disability/global developmental delay and epilepsy (ID/GDD-EP) is very common in pediatric population. The etiologies for both conditions are complex and largely unknown. The predictors of significant copy number variations (CNVs) are known for the cases with ID/GDD but unknown for those with exclusive ID/GDD-EP. Importantly, the known predictors are largely from the same ethnic group hence they lack replication. Purpose: We aimed to determine and investigate the diagnostic yield of CNV tests, new causative CNVs, and the independent predictors of significant CNVs in Chinese children with unexplained ID/GDD-EP. Materials and methods: 100 pediatric patients with unexplained ID/GDD-EP and 1,000 healthy controls were recruited. The American College of Medical Genetics guideline was used to classify the CNVs. Additionally, clinical information was collected and compared between those with significant and non-significant CNVs. Results: 28% of the patients had significant CNVs, 16% had variants of unknown significance and 56% had non-significant CNVs. 31 CNVs were identified in 28% (28/100 cases): 25 pathogenic and 6 likely pathogenic. 18 known syndromes were diagnosed in 17 cases. 13 rare CNVs (8 novel and 5 reported in literature) were identified, three of them span dosage sensitive genes: 19q13.2 deletion (ATP1A3), Xp11.4-p11.3 deletion (CASK) and 6q25.3-q25.3 deletion (ARID1B). By comparing clinical features in patients with significant CNVs against those with non-significant CNVs, a statistically significant association was found between the presence of significant CNVs and speech and language delay for those aged above 2 years, and for those with facial malformations, microcephaly, congenital heart disease, fair skin, eye malformations, and mega cisterna magna. Multivariate logistic regression analysis allowed the identification of two independent significant CNV predictors: eye malformations and facial malformations. Conclusion: Our study supports the performance of CNV tests in pediatric patients with unexplained ID/GDD-EP as there is high diagnostic yield which informs genetic counselling. It adds 13 rare CNVs (8 novel) which can be accountable for both conditions. Moreover, congenital eye and facial malformations are clinical markers that can aid clinicians understand which patients can benefit from the CNV testing and which won`t, thus helping patients avoid unnecessary and expensive tests.